(untitled) (International scientific-electronic journal “Pioneering studies and theories”, 2026)
This study examines how university students in Uzbekistan engage with and perceive online marketing strategies on the Uzum application, a rapidly growing digital platform in the country’s evolving digital economy. Using a qualitative research design, semi-structured interviews were conducted with twelve students to explore their experiences, interpretations, and responses to Uzum’s marketing features. Thematic analysis revealed four major patterns: perceived usefulness and convenience, trust and credibility, personalization and relevance, and user frustration due to ad fatigue. Findings indicate that while students appreciate time-saving promotions and personalized recommendations, their engagement is shaped by the transparency of prices, consistency of marketing messages, and prior experiences with the platform. However, excessive notifications and irrelevant recommendations can reduce satisfaction and trust. Overall, the study highlights the importance of user-centered marketing approaches and provides insights for digital platforms seeking to enhance engagement among young consumers in emerging digital markets.